Penyuluhan Hipertensi dan Diet Hipertensi Pada Warga di Kelurahan Batusari Kota Tangerang - Haerani, Beti; Deswita, Reni (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Hypertension is an increase in blood pressure more than 140/90 mmHg. BatusariSubdistrict Based on a survey conducted by nursing professional students in 2023 in RW 04, Batusari subdistrict, Tangerang City sub-district with 230 samples using the interview method or distributing questionnaires and the highest health problem results were found, namely hypertension at 54.6%. Meanwhile, attitudes towards hypertension were 21.6% in the poor category and hypertension behavior was 69.1% in the poor category and data from interviews conducted by students with the community in RW 04 resulted in the community still not knowing what hypertension is, the signs and risks of hypertension. Based on these findings, we need to plan nursing and health actions to overcome and maintain public health conditions through hypertension education and hypertension diet to improve attitudes and behavior regarding hypertension in BatusariVillage, Tangerang District. This service activity is provided in the form of health education in the form of seminars. The educational material provided is about; the concept of hypertension, prevention, hypertension diet and hypertension exercise demonstrations, this material is presented using lecture and discussion methods. Empowerment activities for cadres and residents through discussions and seminars related to hypertension have had a positive impact, namely increasing residents' knowledge and attitudes about how to treat and prevent hypertension.